Science, technology, and society - Aldea, Kathryn Idrisha; Caronan, Hans Peter A.; Candido, Ma. Blessilda O. (Mandaluyong City : Books Atbp. Publishing, 2018)
"This module is based on outcome based education curriculum which help students to develop their competencies and skills on communication, creativity, critical thinking and problem solving."--Book
Unit 1 Introduction to science, technology and society -- Unit 2 Science, technology & society from the perspective of history -- Unit 3 Current issues arising from the application of science and technology.
Includes bibliographical references.
Keywords: SCIENCE AND CIVILIZATION; TECHNOLOGY -- SOCIAL ASPECTS